1999
DOI: 10.1034/j.1399-3054.1999.105122.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐stimulated ribosomal protein synthesis in maize embryonic axes during germination

Abstract: Addition of insulin to maize seed (Zea mays L. cv. Chalqueño) was found to accelerate germination and seedling growth. Insulin‐stimulated maize axes showed enhancement of S‐methionine incorporation into ribosomal proteins (rp) and mobilization of S6 rp mRNA into polysomes. Increase in S6 rp phosphorylation of the small ribosomal subunit (40S) was observed in P‐orthophosphate pulse‐labeled experiments when maize axes were stimulated by insulin. Application of either wortmannin or rapamycin, inhibitors of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 49 publications
3
34
0
3
Order By: Relevance
“…Insulin and insulin-like growth factors (IGFs), widely distributed among eukaryotic organisms (26), stimulate a signal transduction pathway that targets p70 S6K activation and the subsequent S6rp phosphorylation on the 40S ribosomal subunit (5). Because it has been shown that insulin induces maize S6rp phosphorylation in growing tissues (12), the insulin effect on ZmS6K activity was measured in maize embryonic axes germinated for 24 h. For these experiments, Crude extracts from each axes set were prepared and the same amount of proteins as in A) were resolved in the 2D electrophoresis and analyzed by Western blot (upper panels) and autoradiography (lower panels). The asterisk marks a protein that was nonspecifically recognized by the antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin and insulin-like growth factors (IGFs), widely distributed among eukaryotic organisms (26), stimulate a signal transduction pathway that targets p70 S6K activation and the subsequent S6rp phosphorylation on the 40S ribosomal subunit (5). Because it has been shown that insulin induces maize S6rp phosphorylation in growing tissues (12), the insulin effect on ZmS6K activity was measured in maize embryonic axes germinated for 24 h. For these experiments, Crude extracts from each axes set were prepared and the same amount of proteins as in A) were resolved in the 2D electrophoresis and analyzed by Western blot (upper panels) and autoradiography (lower panels). The asterisk marks a protein that was nonspecifically recognized by the antibody.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the insulin-like protein isolated from B. variegata leaves on glucose levels in the serum of diabetic mice was demonstrated by intravenous injection of the protein fraction extracted from electrophoresis gels. This fraction caused a significant decrease in blood glucose levels in diabetic mice similar to that isocitrate lyase, and malate synthase) involved in the conversion of stored fat to carbohydrate in the fat-storing seed species, sunflower (Helianthus annuus), watermelon (Citrullus vulgaris) and cucumber (Cucumis sativus) (31) and to induce ribosomal protein synthesis and seedling development from maize seeds (32). Yet, despite the lack of direct evidence of insulin effects on carbohydrate metabolism in plants, many literature reports suggest the existence of proteins with functions, localization and sequences of the corresponding gene or protein similar to proteins that are members of the insulin pathways characteristic of vertebrates (23).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, apart from the many reports on the lowering of blood sugar levels in diabetic animals by extracts of plant parts (4,16,17), no place for insulin as a member of signaling pathways has been suggested by researchers in the fields of glucose mobilization or transport (18)(19)(20)(21). Nevertheless, it has been shown that added insulin increases germination of some seeds (22; Oliveira AEA and Xavier-Filho J, unpublished results), accelerates synthesis of ribosomal proteins in germinating maize embryos (23,24), and increases the activity of glyoxysomal enzymes involved in the conversion of fat to carbohydrate in maize (22).…”
Section: Introductionmentioning
confidence: 99%